Perspektif Guru Terhadap Pembelajaran Bahasa Inggris Berbasis Pembelajaran Daring MI Ihyaul Islam Bolo Ujungpangkah Gresik - Rohmah, Sirli Fuadah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
The current pandemic has resulted in a change in the implementation of learning from conventional learning to an online or distance learning. This was done after the circulation of a decree from the Minister of Education and Culture Nadiem Makarim at number 36962/MPK.A/HK/2020 so that it requires all educational institutions to implement distance learning. In addition to the regulation, it caused the researcher to take a research to find out the learning concepts used by the English teachers and their perspectives on implementing online learning or distance learning.The objectives of this study are: 1) To see the concepts that the teachers apply in online-based English learning to students of Madrasah Ibtidaiyyah. 2) To see the teachers’ perspective in teaching online-based English learning to students of Madrasah Ibtidaiyyah.The research method used by researcher is qualitative methods, and the data collection techniques are interviews, questionnaires and documentation. The technique of selecting informants using purposive sampling is shown to the English teacher so that the information obtained is valid. In-depth interviews were conducted through direct interviews. Additionally, the researcher also does the data triangulation method then use the theory of teaching English in using distance learning method and English learning for elementary schools.The results showed that: 1) the learning concept applied at this time is the teachers used the WhatsApp application to deliver material and there were changes to the learning tools according to the online-based learning. 2) The teachers’ perspective in implementing distance learning shows that the teachers think that conventional learning is more effective than online or distance learning.